Leave no trace [videorecording (DVD)] - Granik, Debra; McKenzie, Thomasin, 2000-; Foster, Ben, 1980-; Kober, Jeff, 1953- (Universal Pictures Home Entertainment, 2018)
Will and his teenage daughter, Tom, have lived off the grid for years in the forests of Portland, Oregon. When their idyllic life is shattered, both are put into social services. After clashing with their new surroundings, Will and Tom set off on a harrowing journey back to their wild homeland.